Chromosomal Evolution in the Phylogenetic Context: A Remarkable Karyotype Reorganization in Neotropical Parrot Myiopsitta monachus (Psittacidae) - Furo, Ivanete de Oliveira; Kretschmer, Rafael; O’Brien, Patricia Caroline; Pereira, Jorge C.; Garnero, Analía del Valle; Gunski, Ricardo José; O’Connor, Rebecca E.; Griffin, Darren Karl; Gomes, Anderson José Baia; Ferguson-Smith, Malcolm Andrew; de Oliveira, Edivaldo Herculano Correa (Frontiers in Genetics, 2020)
Myiopsitta monachus is a small Neotropical parrot (Psittaciformes: Arini Tribe) from subtropical and temperate regions of South America. It has a diploid chromosome number 2n=48, different from other members of the Arini Tribe that have usually 70 chromosomes. The species has the lowest 2n within the Arini Tribe. In this study, we combined comparative chromosome painting with probes generated from chromosomes of Gallus gallus and Leucopternis albicollis, and FISH with bacterial artificial chromosomes (BACs) selected from the genome library of G. gallus with the aim to shed light on the dynamics of genome reorganization in M. monachus in the phylogenetic context. The homology maps showed a great number of fissions in macrochromosomes, and many fusions between microchromosomes and fragments of macrochromosomes. Our phylogenetic analysis by Maximum Parsimony agree with molecular data, placing M. monachus in a basal position within the Arini Tribe, together with A. aestiva (short tailed species). In Myiopsitta monachus many chromosome rearrangements were found to represent autopomorphic characters, indicating that after this species split as an independent branch, an intensive karyotype reorganization took place. In addition, our results show that M. monachus probes generated by flow cytometry provide novel cytogenetic tools for the detection of avian chromosome rearrangements, since this species presents breakpoints that have not been described in other species.